(untitled) (Modern education and development, 2025)
As digital technologies have grown in popularity, education has changed dramatically, and online learning is now more often used in addition to traditional offline education. There are clear benefits and difficulties to both learning approaches. Offline learning improves direct involvement and structured learning experiences, whereas internet learning offers flexibility and accessibility. This study looks at how students’ academic performance, engagement, and information retention are affected by both online and offline learning. According to the results, a blended learning strategy can enhance the overall educational experience by combining the advantages of both approaches